INTEGRATION OF PROPHETIC VALUES IN EDUCATION AT METRO MUHAMMADIYAH UNIVERSITY - Ardiwansyah, Bayu; Mawangir, Muh.; Abdurrahmansyah, Abdurrahmansyah (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: This study is motivated by the need to develop an educational paradigm that not only focuses on character education but also expands its scope by integrating prophetic values into the education system. Purpose: The study examines the implementation of prophetic values (ṣiddīq, amānah, tablīgh, faṭānah) at Universitas Muhammadiyah Metro (UM Metro). Method: Using a qualitative approach and grounded theory methodology, data was collected through interviews, documentation, and observations, and analyzed using Miles & Huberman's interactive model. Result: The findings reveal that prophetic values are integrated into the curriculum through the